Aplikasi Sistem Informasi Job Order Costing Berbasis Web - Teguh Setiadi; Nopiah Widaningsih (Teknik: Jurnal Ilmu Teknik dan Informatika, 2021)
The rapid development of science and information technology has become one of the driving factors and has a very important role in economic development. The existence of increasingly sophisticated technology allows users to make use of appropriate technology. One of them is by building an accounting information system. The use of an Order Costing System or an order-based costing system is used by companies that make relatively small quantities of different products or services according to specifications designed by the buyer. Job order Costing Method With this system, it will be easier to calculate the cost of goods manufactured at J-Zipper Convection. Using this system will also make it easier to group production data. This system will also make it easier to manage because it uses an online system. With the job order costing method in this system, the calculation of the cost of goods manufactured is more in line with the costs incurred and produces accurate reports.